To the History of Establishing a Nuclearfree zone in Central Asia: the Character of International Cooperation in Light of its Formation - A. M. Ibragimov; G. N. Nutsalhanov (Московский журнал международного права, 2012)
The process of establishing a nuclear-free zone in Central Asia ended, and was held in difficult conditions. In present article analyzes the difficulties of her contractual fixation, considered the positions of States in this question, which have great importance for ensuring strategic stability and security in the region and the world. The authors give their analysis of the situation, and are suggesting the ways of the completion of implementation of the idea of establishing a zone in the region, guaranteeing the extension space of non-proliferation of nuclear weapons.